Accountability and Transparency in Financial Management of Village Fund Allocations in Achieving Good Governance - Bakhtiar Bakhtiar (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The Purpose of the research objective is to provide insight that can determine the management of village fund allocations (ADD) through the principles of good accountability and transparency. The type of research used is qualitative data, namely data expressed in the form of words, sentences, and documents or archives regarding the management of village fund allocations regarding accountability and transparency in realizing good governance in Tanete Village Tompobulu District, Gowa Regency. Sources of data used are primary data and secondary data. The data analysis method used in this research is descriptive analysis in written and spoken words that can be observed in words, sentences or pictures, and data. The results of this study are the supervision of ADD financial management carried out by the BPD as a supervisor whose function is to set village regulations, and the village head has carried out his duties well. The BPD's supervision of ADD financial management has been carried out as much as possible, marked by the development of village infrastructure sourced from ADD.